Theperceptions of patients with osteoarthritis at a public community rehabilitation centre in the Cape Metropole for using digital technology in rehabilitation - Prins, Gabriela (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScPhysio)--Stellenbosch University, 2024.